If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + -12 = 24 Reorder the terms: -12 + Y = 24 Solving -12 + Y = 24 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + Y = 24 + 12 Combine like terms: -12 + 12 = 0 0 + Y = 24 + 12 Y = 24 + 12 Combine like terms: 24 + 12 = 36 Y = 36 Simplifying Y = 36
| 7=4(5-2x)+3y | | 3(h-4)=-.5(24-6h) | | 7(3x-2)+18x+7=12x+7 | | (4n+17)+(n-2)=180 | | 9+t=14 | | (x+4)(x+4)+6=87 | | x+2=2x+15 | | 20+(-26)+34-(-37)-62= | | 10x^2+15x-8x-12=0 | | 3(x-3)+4(x)=9 | | 3*b-4=5v-2 | | (12x^2)-4x-5=0 | | 2(w-8)=4 | | 11.2j+11.55=j+10.1j+10.35 | | 13x+13=5x+11 | | x(x-20)=-20(2x+5) | | (2a+5)(a-6)= | | (15x^2+70x+25)=0 | | 2*s+3*s-1=18 | | 2(x+5)=3(x-(2-x)) | | 6*h+4=-2h | | 3(6+5x)=2(-5+4x) | | x^2-8x-84=0 | | -3=3(c+9) | | y=-3X^2-12X-11 | | (x^2)-12x+35=0 | | 2(x+5)=3[x-(2-x)] | | (A(A+4))=140 | | 5g=q+5u | | 24+(-52)+47-(-55)-70= | | (13x+10)+2x=90 | | 1-4p=1+2p |